Linguistic substantiation of learning Russian pronunciation (from work experience by teaching Lithuanian students) - Plakunova, T. (Psichologija, 1963)
1. When teaching the Russian language to Lithuanian students, it is important not only to develop their skills to correctly pronounce the sounds of Russian, but also to teach them correct writing in Russian. 2. When teaching the literary pronunciation of the Russian language to Lithuanians, it is not advisable to teach them pronounce single separate sounds. Because every sound occupies a certain place in the language system, improvement of correct pronunciation of sounds must rely on comparison of phonetic and phonological systems of the Russian and Lithuanian languages. 3. The method of comparison requires the learner’s conscious control of articulation unconventional to him/her and simultaneous refusal of pronunciation of sounds of own mother tongue when assimilating the sounds of a studied language. It is especially difficult to control such sounds and sound combinations of a learned language which at first seem to be similar to one’s mother tongue, but actually such “similarity” is only supposed. 4. When teaching Lithuanians to pronounce vowels of the Russian language, attention should be firstly paid to the following aspects: a) General lax of the organs of speech b) Qualitative change of Russian vowel sounds in unstressed position and elongation of vowels depending on their position c) Qualitative promiscuity of vowels, the tendency of stressed Russian vowels to breaking, the influence of the phonetic environment on the quality of vowels (especially on the vowel e) 5. When teaching Lithuanians to pronounce the consonants of the Russian language, the attention should be paid to assimilation of: a) the hushing ш and ж before u and pronunciation of e, also the pronunciation of ш and ж in combinations шё and жё; b) pronunciation of the soft consonants т’ and б’ , especially before vowels u and e; c) pronunciation of the consonant л before the soft consonants and pronunciation of the soft л‘ before hard consonants; d) pronunciation of the soft consonants at the end of the word, especially of the soft consonant ф‘; e) the character of consonant palatalization before vowels u and e; f ) assimilation of the pronunciation of long consonants, first of all, in morpheme junctions and a consonant with the subsequent compound.